PENERAPAN PRINSIP KEHATI-HATIAN DALAM PERJANJIAN KREDIT MIKRO MODAL KERJA PADA PT BANK PERKREDITAN RAKYAT AMBARKETAWANG PERSADA YOGYAKARTA - , Marya Biadila. SH; , Hariyanto, S.H., M.Kn., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Writing this thesis aims to examine the application of prudential banking principle in working capital loan agreement at the rural bank Ambarketawang Persada Yogyakrta that serve at the basic consideration in providing micro-credit for working capital. And to identify and assess measure to be carried out the rural Bank Ambarketawang Persada Yogyakarta when the debtor default suffered promise and causing micro-credit working capital problems. This research includes empirical juridicial research, which is the approach to a problem with looking at and concered theapplicable rule of law, linked with the phenomena of the problems found in the research. Data collections techniques in research literatute is condected by studies document that is a data collection technique or mode by studying the literature, either in the form of books,studies, and regulations with regard to the principle of prudent banks in providing credit and associated with the agreement. Primary and secondary data will be qualitative analyzed with systematically arranged and inductive method was with drawn in each problem formulation conclusion. Fieldwork was conducted by means of interviews using an interview guide. The result of basic consideraration bank perkreditan rakyat ambarketawang persada Yogyakarta apply the prudential banking in delivering micro creditfor working capital based on the 5 Câs credit analisys that is from character, capital, capacity, collateral and conditions of economic. And should be consider too about constraint aspect, but in practice in the bank perkreditan rakyat ambarketawang persada Yogyakarta more emphasis about guarantee aspect and debitor capacity in delivery working capital based kredit. The legal action to resolve bad credit bay parate executie, parate executie is sell it own by debtor to get higher price, and wit fiat executie throught an auction that has a court warrant.